Pembiayaan Usaha Rakyat Terhadap Pertumbuhan Usaha Non- Muslim: Studi Empiris di Kota Banda Aceh - Cut Rizka Kamila; Hafas Furqani; Nevi Hasnita (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
Islamic banks whose operations are based on sharia principles offer financing products that not only attract Muslims but also attract non-Muslims. One of the financing products available at BSI is the People's Business Credit (KUR). The purpose of this research is to see how the implementation, the role of financing, and the views of non-Muslims towards KUR financing. This research is a qualitative research. The results of the study found (1) the implementation of financing at BSI KCP Peunayong 3 using a murabaha contract, the concept of murabaha contract is used through a murabaha bil wakalah contract. The customer selection procedure uses the 5 C principle (Character, Capital, Capacity, Collateral, and Condition). (2) The role of business financing applied by Bank Syariah Indonesia KCP Peunayong 3 brings benefits to the community, especially to non-Muslim entrepreneurs who take financing at the BSI. It can be seen from the growth of non-Muslim businesses that have increased turnover from 10% - 30% after taking KUR financing, customer growth has increased by 20% -50% and labor has increased insignificantly. (3) Opinions of non-Muslim entrepreneurs on KUR financing at BSI KCP Peunayong 3, namely: The principle of speed of process, the principle of justice, the principle of convenience.